2014
DOI: 10.1002/art.38403
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Modulates the Phenotype of Osteoblasts Isolated From Knee Osteoarthritis Patients, Leading to Undermineralized Bone Nodule Formation

Abstract: ObjectiveTo investigate the role of hypoxia in the pathology of osteoarthritic (OA) bone by exploring its effect on the phenotype of isolated primary osteoblasts from patients with knee OA.MethodsOA bone samples were collected at the time of elective joint replacement surgery for knee or hip OA. Normal bone samples were collected postmortem from cadaver donors. Primary osteoblasts were isolated from knee OA bone chips and cultured under normoxic or hypoxic (2% O2) conditions. Alkaline phosphatase activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
(59 reference statements)
3
25
0
Order By: Relevance
“…In Tg6 mice, the increase in EPO levels is similar to the stimulation of EPO at high altitude (45). This model is also relevant for the pathophysiologic increase of endogenous EPO levels observed after bleeding/repeated phlebotomies without the confounding direct effect of hypoxia on bone cells (46) and in cases of paraneoplastic production of EPO (47), thalassemia, and polycythemia vera (48). On the other hand, the 30U‐inj model is relevant for therapeutic administration of exogenous EPO (16, 18).…”
Section: Discussionmentioning
confidence: 99%
“…In Tg6 mice, the increase in EPO levels is similar to the stimulation of EPO at high altitude (45). This model is also relevant for the pathophysiologic increase of endogenous EPO levels observed after bleeding/repeated phlebotomies without the confounding direct effect of hypoxia on bone cells (46) and in cases of paraneoplastic production of EPO (47), thalassemia, and polycythemia vera (48). On the other hand, the 30U‐inj model is relevant for therapeutic administration of exogenous EPO (16, 18).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that hypoxic regulation of Angptl4 expression in osteoblasts is mediated by the HIF1a pathway. Angptl4 has previously been shown to be HIF1a regulated in cardiomyocytes, adipocytes, endothelial cells, osteoblasts, and osteoclasts . In a study of human osteoblasts isolated from the knee of osteoarthritic patients, Angptl4 mRNA expression increased under hypoxic conditions (2% O 2 ) and in cells treated with the hypoxia mimetic dimethyl‐oxalylglycine (DMOG) …”
Section: Discussionmentioning
confidence: 99%
“…Its effect on angiogenesis and vascular permeability seems to be dependent on the method and form of the protein used, with both proangiogenic and antiangiogenic effects shown . Angptl4 has been shown to be upregulated during hypoxia in articular chondrocytes, osteoclasts, osteoblasts, cardiomyocytes, adipocytes, endothelial cells, and brain tissue . Of those cell types where Angptl4 expression was elevated by hypoxia, it was also shown to be HIF regulated in cardiomyocytes, adipocytes, endothelial cells, osteoblasts, and osteoclasts .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia also increases the osteoblast production of PGE2, cyclooxygenase 2, angiopoietin‐like 4, type II collagen α1 chain, and insulin‐like growth factor binding protein 1. Moreover, an in vitro study, by using culture of primary osteoblasts isolated from knee bone from patients affected by osteoarthritis, has demonstrated that hypoxia modifies osteoblast phenotype, including the expression of genes that regulate bone matrix, bone remodeling, and bone vasculature (Chang, Jackson, Wardale, & Jones, ).…”
Section: Introductionmentioning
confidence: 99%